Rhynchosia bolusii (Phaseoleae, Fabaceae), a new species from the Western Cape Province of South Africa - Boatwright, James Stephen; Moteetee, Annah Ntsamaeeng (Phytotaxa, 2014)
A new species, Rhynchosia bolusii, is described. It is closely similar to R. capensis in the details of its leaves and long, slender peduncles, but differs mainly in its shrubby, non-twining habit and few-flowered inflorescences. It is known only from the summit of the Great Swartberg Mountains in the Western Cape Province.